2021
DOI: 10.1002/ase.2134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of compulsory participation of medical students in a multiuser online game to learn radiological anatomy and radiological signs within the virtual world Second Life

Abstract: Competitive game-based learning within Second Life enables effective teaching of basic radiological anatomy and signs to medical students, with good acceptance and results when students participate voluntarily, but unknown in a compulsory context. The objectives of this study were to reproduce a competitive online game based on self-guided presentations and multiple-choice tests in a mandatory format, to evaluate its development and student perceptions compared to a voluntary edition in 2015 (N = 90). In 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…With the technological development of digital radiographic reconstruction with geometric as well as density characteristic accuracy ( 107 ), more and more VS computer software programs have been designed and used in undergraduate medical education, allowing students gain more hands-on experience and develop their clinical skills without worrying about exposing to any unnecessary radiation. In the recent 2 years, we found five studies ( 20 , 85 , 86 , 88 , 96 ) used VS serious games or systems simulating a radiologist’s practice in the real world among medical undergraduates for radiology learning. The results collectively showed that, for medical undergraduates, the integration of VS as a valuable learning resource had the potential to improve preparation for the clinical environment and increase student confidence ( 20 , 85 , 86 , 88 , 96 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the technological development of digital radiographic reconstruction with geometric as well as density characteristic accuracy ( 107 ), more and more VS computer software programs have been designed and used in undergraduate medical education, allowing students gain more hands-on experience and develop their clinical skills without worrying about exposing to any unnecessary radiation. In the recent 2 years, we found five studies ( 20 , 85 , 86 , 88 , 96 ) used VS serious games or systems simulating a radiologist’s practice in the real world among medical undergraduates for radiology learning. The results collectively showed that, for medical undergraduates, the integration of VS as a valuable learning resource had the potential to improve preparation for the clinical environment and increase student confidence ( 20 , 85 , 86 , 88 , 96 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the recent 2 years, we found five studies ( 20 , 85 , 86 , 88 , 96 ) used VS serious games or systems simulating a radiologist’s practice in the real world among medical undergraduates for radiology learning. The results collectively showed that, for medical undergraduates, the integration of VS as a valuable learning resource had the potential to improve preparation for the clinical environment and increase student confidence ( 20 , 85 , 86 , 88 , 96 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations